The Influence of Financial Literacy, Financial Attitude and Financial Planning on Financial Management of Students at Cokroaminoto University, Palopo - Haq, Muhammad Fauzan; Bachri, Samsul; Sahrir, Sahrir (Trunojoyo University of Madura, 2025)
The purpose of this study is to determine how financial literacy, financial attitude, and financial planning affect the financial management of students enrolled at Cokroaminoto Palopo University's physics program. employing a quantitative methodology and information gathered from an online survey with 80 participants, with an emphasis on students as research subjects. Multiple linear regression was used for data analysis in order to assess each variable's contribution to financial management. The study's findings indicate that student financial management is significantly impacted by financial literacy, financial attitude, and financial planning. These results demonstrate the significance of financial literacy, financial attitude, and financial planning in student financial management.